Sub-MIC Tylosin Inhibits Streptococcus suis Biofilm Formation and Results in Differential Protein Expression - Wang, Shuai; Yang, Yanbei; Zhao, Yulin; Zhao, Honghai; Bai, Jingwen; Chen, Jianqing; Zhou, Yonghui; Wang, Chang; Li, Yanhua (Frontiers in Microbiology, 2016)
Streptococcus suis (S. suis) is a crucial zoonotic pathogen which causes severe diseases in humans and pigs. Biofilms of S. suis can induce persistent infections which are harder to treat. Sub-minimal inhibitory concentration (sub-MIC) of tylosin can inhibit biofilm formation in bacteria. By using iTRAQ strategy, we compared the protein expression profiles of S. suis grown with sub-MIC tylosin treatment or no treatement. The result showed that 96 proteins expression were changed with 77 up-regulated and 19 down-regulated proteins. Several metabolism proteins (such as phosphoglycerate kinase), as well as cell surface proteins (such as ABC transporter proteins), were found to be involved in biofilm formation. Overall, our results indicated that S. suis metabolic regulation, cell surface proteins, and virulence proteins appear to be of importance in biofilm growth by sub-MIC tylosin treated. Thus, our data analyzed rough regulation of biofilm formation that lay the foundation for the future research of mechanism and targets.